Rules of capture and transport of wisents from Poland to other European countries (European Bison Conservation Newsletter, 2016)
Over 90 years after the appeal at the Congress in Paris about undertaking all necessary measures in order to protect the wisent population in Europe, the number of this species has risen to 6083 individuals (EBPB 2016). It demonstrates the success of numerous programs of reintroduction and protection; nevertheless, the wisent is still regarded as an endangered species categorized as Vulnerable D1 (Olech 2008a). The management of the wisent population is targeted at preservation of genetic diversity in existing herds and creation of new captive and free living herds. Such management method consists of capturing and relocating animals between breeding centers and free living herds. Transportation of animals requires appropriate preparation due to breeding and logistic reasons, as well as high investment costs. The necessity of publishing the transport rules results from the needs of people involved in protection of the wisent. This paper presents a collection of rules recommended by the European Bison Conservation Center concerning the wisent transportation with the application of best practices, such as carrying animals in wooden containers and loading animals to containers without the use of drugs.
Keywords: Bison bonasus; transportation; capture; safety rules